2013
DOI: 10.1111/ijn.12039
|View full text |Cite
|
Sign up to set email alerts
|

Achieving peace and harmony in life: Thai Buddhists living with HIV/AIDS

Abstract: This study aimed to reveal the process of achieving peace and harmony in life by Thai Buddhists living with HIV/AIDS in Southern Thailand. Data were gathered from 28 Thai Buddhist participants aged 18 years or older, who had lived with HIV/AIDS for 5 years or more. Purposive, snowball and theoretical sampling techniques were used to recruit the participants. Data collection, using in‐depth interviews, was carried out over a 7 month period between 2011 and 2012. Grounded theory was used to guide the process of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…Understanding the disease and accepting truth in life is a unique and important attribute of spirituality and dignity of people living with HIV in the Thai context (Balthip 2010;Balthip et al 2013). Although the participants in this study are adolescents aged 15-19 years old, they understood and accepted the truth of having HIV and the truth about life and death.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Understanding the disease and accepting truth in life is a unique and important attribute of spirituality and dignity of people living with HIV in the Thai context (Balthip 2010;Balthip et al 2013). Although the participants in this study are adolescents aged 15-19 years old, they understood and accepted the truth of having HIV and the truth about life and death.…”
Section: Discussionmentioning
confidence: 95%
“…The concerning towards other and the society can be presented in three ways; prevention of spreading HIV to others, avoiding being a burden to others, and avoiding making significant others feel sad about loss. The responsibility to the society that they present will minimize the negative image and stigmatization of people living with HIV, reflected the sense of compassion to others (Balthip et al 2013). This responsibility is mainly represented in the dignity of moral stature that is tied to self-respect.…”
Section: Discussionmentioning
confidence: 99%
“…Several themes emerge in this literature: religion as a source of support [29], spirituality as a barrier to/facilitator of treatment [30, 31], personal faith as a coping strategy [28, 30], and spirituality in palliative AIDS care [27]. Although these themes are similar to those found in the West, it is encouraging to see such research in various geographic settings.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the participants described that the sources of spiritual support resulted from believing in God .3,7-8,26,28-31 On the other hand, PLWHA in Thailand indicated that the source of spirituality came from religious practice, family support and adherence to the Lord Buddha's teachings. [9][10][11]27 The above factors provided the PLWHA with the power to manage stressful life events and illness. The participants described the positive roles of spirituality in life.…”
Section: Discussionmentioning
confidence: 99%
“…The Roles of Spirituality in People Living with HIV/AIDS: A Qualitative Meta-synthesis Seeger, 2007 26 Foster et al, 201 13 Tawaisab, 2011 27 Mbetbo, 201 37 Caixeta et al, 2012 28 Dalmida et al, 2012 29 Balthip et al 8,28 ; peaceful 7,9,27 ; happiness 27 -inner strength 8,27,29, ; self-control8; empowerment 3,8 ; keep going 28,29 ; relieve the fear of death 8 ; self-consciousness 27 -understanding and accepting illness [8][9]11,30 ; reduce self-blame, self-acceptance, self-forgiveness 8,26,28 ; self-esteem 26 -self-healthcare 8,11,30 -sympathy, empathy, compassion 3,27 ; responses for others 11 -purposes of life 11 -maintaining hope 11 , making choice, second chance 11,28 -social support, sense of belonging [7][8]26 ; connect with god or higher power 7,8,[28][29][30][31] -feeling guilty 7…”
Section: Identifying Associations Among the Studiesmentioning
confidence: 99%